Future-Oriented Coping with Weather Stress among Mountain Hikers: Temperamental Personality Predictors and Profiles - Piotr Próchniak; Agnieszka Próchniak (Behavioral Sciences, 2021)
The aim of the study was to explore temperamental personality traits as predictors of fu-ture-oriented coping with weather stress in a group of Polish mountain hikers. The subjects were 209 young mountain hikers (M = 21.20; SD = 3.70) who took three temperament–personality questionnaires, i.e., FCZ-KT Temperament Questionnaire, Sensation Seeking Scale IV and NEO-FFI- Personality Inventory, alongside a recently constructed scale for diagnosing future-oriented coping with weather stress in outdoor context, Preventive and Proactive Coping with Bad Weather Scale in Outdoor Sports. The regression analysis indicated that preventive coping with weather stress in hiking was predicted by activity, emotional reactivity, briskness, sensory sensitivity, experience seeking, agreeableness and conscientiousness. In turn, proactive coping with bad weather in hiking was predicted by endurance, activity, thrill and adventure seeking and extraversion. In turn, the cluster analysis revealed three distinct clusters of hikers characterized by diverse re-sults on the scales of preventive and proactive dealing with adverse weather, namely, prudent hikers (high preventive coping/high proactive coping), reckless hikers (low pre-ventive coping/high proactive coping) and wary hikers (high preventive coping/low proactive coping). The hikers in these clusters differed in terms of temperamental per-sonality traits.